2022
DOI: 10.3390/vaccines10030446
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Humoral Responses after the Second Dose of mRNA BNT162b2 Vaccine in Residents of a Long Term Care Facility

Abstract: Residents of long-term care facilities (LTCFs) have been dramatically hit by the COVID-19 pandemic on a global scale as older age and comorbidities pose an increased risk of severe disease and death. The aim of the study was to assess the quantity and durability of specific antibody responses to SARS-CoV-2 after the first cycle (two doses) of BNT162b2 vaccine. To achieve this, SARS-CoV-2 Spike-specific IgG (S-IgG) titers was evaluated in 432 residents of the largest Italian LTCF at months 2 and 6 after vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The correlation of both IgG and neutralising antibody concentrations with disease intensity shows that even if antibody concentrations are not high enough to protect from infection, they can reduce the severity of disease. Overall, the results of this study, together with the shown waning of humoral response following the second vaccine dose, 6 , 17 highlight the importance of high antibody concentrations for protection against SARS-CoV-2 infection. Booster doses—which have been shown to be effective for increasing antibody concentrations, 18 , 19 —are currently the most important course of action for increased protection against infection.…”
Section: Discussionmentioning
confidence: 58%
“…The correlation of both IgG and neutralising antibody concentrations with disease intensity shows that even if antibody concentrations are not high enough to protect from infection, they can reduce the severity of disease. Overall, the results of this study, together with the shown waning of humoral response following the second vaccine dose, 6 , 17 highlight the importance of high antibody concentrations for protection against SARS-CoV-2 infection. Booster doses—which have been shown to be effective for increasing antibody concentrations, 18 , 19 —are currently the most important course of action for increased protection against infection.…”
Section: Discussionmentioning
confidence: 58%
“…The currently approved and available vaccines have different mechanisms of action in triggering the immune system to produce immune response biomarkers that predict vaccine effectiveness. Several studies have discussed the vaccine effect of various vaccine types on inducing immune responses to produce immune biomarkers and their durability (4)(5)(6)(7)(8). However, these studies were limited in examining the effect of whole inactivated vaccine, the effect of vaccine mixing between more than one type, and the change in immunity levels by the number and type of the received vaccine doses on different forms of immunity.…”
Section: Introductionmentioning
confidence: 99%
“…This nding is supported by previous reports (7-9). Lai et al showed a decrease in the median antibody titer between 2 and 6 months after the second COVID19 vaccination (7). This has also been reported post infection (10).…”
Section: Discussionmentioning
confidence: 63%